Transient protein losing enteropathy associated with acute gastritis and campylobacter pylori. Issue 12 (December 1987) - Hill, I D; Sinclair-Smith, C; Lastovica, A J; Bowie, M D; Emms, M
Abstract : Three children presented with acute protein losing enteropathy and were found to have acute gastritis associated with Campylobacter pylori infection. Recovery from protein losing enteropathy was accompanied by resolution of the gastritis and the disappearance of C pylori from the gastric mucosa. Their clinical course suggested that the C pylori had caused the gastritis and the protein losing enteropathy. The association between gastritis caused by C pylori and protein losing enteropathy in children has not to our knowledge been previously described.